2020
DOI: 10.3892/ol.2020.12170
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic chemotherapy in non‑small cell lung cancer (Review)

Abstract: Metronomic chemotherapy (MCT) is defined as the rhythmic chemotherapy of low-dose cytotoxic drugs with short or no drug-free breaks over prolonged periods. MCT affects tumor cells and the tumor microenvironment. Particularly, the low-dose schedule impairs the repair process of endothelial cells, resulting in an anti-angiogenesis effect. By stimulating the immune system to eliminate tumor cells, MCT induces immunological activation. Furthermore, combined with targeted therapy, anti-angiogenic drugs enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 95 publications
(95 reference statements)
1
15
0
Order By: Relevance
“…During the last decade, numerous clinical trials have been performed to explore MC in first-and second-line treatment, and to investigate the maintenance of treatment for metastatic NSCLC [27][28][29][30]. Due to lower toxicity, higher tolerability and acceptable safety, MC could be a better option for patients with NSCLC cancer [31]. In our study, the same impact of MTD and MC schedules on in vivo NSCLC tumor growth was reported.…”
Section: Discussionsupporting
confidence: 68%
“…During the last decade, numerous clinical trials have been performed to explore MC in first-and second-line treatment, and to investigate the maintenance of treatment for metastatic NSCLC [27][28][29][30]. Due to lower toxicity, higher tolerability and acceptable safety, MC could be a better option for patients with NSCLC cancer [31]. In our study, the same impact of MTD and MC schedules on in vivo NSCLC tumor growth was reported.…”
Section: Discussionsupporting
confidence: 68%
“…To compare different treatment schemes, we simulated various single and combination therapy schedules based on clinical protocols of MTD and M treatments with short half-life anti-cancer drugs [ 89 ] ( Fig 4 ). A major consideration for treatment design is to limit toxicity to normal tissue, so a hypothetical toxic dose level is indicated by a normalized value equal to 1 in the plots.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of MC, and its therapeutic use, have been extensively reviewed [19][20][21][22][23]25] as regards the treatment of breast cancer [34,35], non-small-cell lung cancer (NSCLC) [36], and high-risk pediatric malignancies [37]. A systematic review on MC compiles the clinical experience in different cancers such as breast, castration-resistant prostate, ovarian, glial, renal, lung, gastrointestinal, hepatocellular, multiple myeloma, melanoma, and head and neck [38].…”
Section: Metronomic Chemotherapy: a Multimodal Therapymentioning
confidence: 99%